The first pineoblastoma case report of a patient with Sotos syndrome harboring NSD1 germline mutation - Xizan Yue; Bo Liu; Tiantian Han; Didi Guo; Ran Ding; Guangyu Wang (BMC, 2024)
Abstract Germline mutations of NSD1 are associated with Sotos syndrome, characterized by distinctive facial features, overgrowth, and developmental delay. Approximately 3% of individuals with Sotos syndrome develop tumors. In this study, we describe an infant in pineoblastoma with facial anomalies, learning disability and mild autism at 1 years diagnosed as Sotos syndrome owing to carrying a novel mutation de novo germline NSD1 likely pathogenic variant. This patient expands both the mutation and phenotype spectrum of the Sotos Syndrome and provides new clinical insights into the potential mechanism of underlying pinealoblastoma pathology.